Field-grown ictB tobacco transformants show no difference in photosynthetic efficiency for biomass relative to the wild type. (13th May 2022) - Ruiz-Vera, Ursula M; Acevedo-Siaca, Liana G; Brown, Kenny L; Afamefule, Chidi; Gherli, Hussein; Simkin, Andrew J; Long, Stephen P; Lawson, Tracy; Raines, Christine A
Abstract : Despite previous studies showing potential for increased plant productivity through overexpression of the inorganic carbon transporter B gene ( ictB ), no significant difference was found between field-grown ictB -expressing tobacco lines and the wild type. Abstract: In this study, four tobacco transformants overexpressing the inorganic carbon transporter B gene ( ictB ) were screened for photosynthetic performance relative to the wild type (WT) in field-based conditions. The WT and transgenic tobacco plants were evaluated for photosynthetic performance to determine the maximum rate of carboxylation ( V c, max ), maximum rate of electron transport ( J max ), the photosynthetic compensation point (Γ*), quantum yield of PSII (ΦPSII ), and mesophyll conductance ( g m ). Additionally, all plants were harvested to compare differences in above-ground biomass. Overall, transformants did not perform better than the WT on photosynthesis-, biomass-, and leaf composition-related traits. This is in contrast to previous studies that have suggested significant increases in photosynthesis and yield with the overexpression of ictB, although not widely evaluated under field conditions. These findings suggest that the benefit of ictB is not universal and may only be seen under certain growth conditions. While there is certainly still potential benefit to utilizing ictB in the future, further effort must be concentrated on understanding the underlying function of the gene and in which environmental conditions it offers the greatest benefit to crop performance. As it stands at present, it is possible that ictB overexpression may be largely favorable in controlled environments, such as greenhouses.